Influence of the number of washings for embryos on non-invasive preimplantation chromosome screening results - Kang, Xiaomei; Wen, Meiting; Zheng, Jie; Peng, Fangxin; Zeng, Ni; Chen, Zhu; Wu, Yanting; Sun, Hong (Frontiers in Endocrinology, 2024)
Objective: To explore the effect of varying numbers of embryo washings prior to blastocyst formation in non-invasive preimplantation chromosome screening (NICS) on the accuracy of NICS results. Methods: In this study, 68 blastocysts from preimplantation genetic testing (PGT)-assisted pregnancy were collected at our institution. On the fourth day of embryo culture, the embryos were transferred to a new medium for blastocyst culture and were washed either three times (NICS1 group) or ten times (NICS2 group). A trophectoderm (TE) biopsy was performed on the blastocysts, and the corresponding embryo culture media were collected for whole genome amplification (WGA) and high-throughput sequencing. Results: The success rate of WGA was 100% (TE biopsy), 76.7% (NICS1 group), and 89.5% (NICS2 group). The success rate of WGA in embryo medium on days 5 and 6 of culture was 75.0% (33/44) and 100% (24/24), respectively. Using TE as the gold standard, the karyotype concordance rate between the results of the NICS1 and NICS2 groups’ embryo culture medium samples and TE results was 43.5% (10/23) and 73.5% (25/34), respectively. The sensitivity and specificity of detecting chromosomal abnormalities were higher in the NICS2 group than in the NICS1 group when TE was used (83.3% vs 60.0%; 62.5% vs 30.8%, respectively). The false-positive rate and false-negative rate (i.e., misdiagnosis rate and missed diagnosis rate, respectively) were lower in the NICS2 group than in the NICS1 group (37.5% vs 69.2%; 16.7% vs 40.0%, respectively). Conclusion: The NICS yielded favorable results after ten washings of the embryos. These findings provide a novel method for lowering the amount of cell-free DNA contamination from non-embryonic sources in the medium used for embryo development, optimizing the sampling procedure and improving the accuracy of the NICS test.